Vehicle Sensing and Localization in Vehicular Networks - Hasan, Nawaid; Aziz, Azlan Abd; Mahmud, Azwan; Alias, Yusoff Bin; Besar, Rosli Bin; Hakim, Luqman; Hamidi, Mohd Adnin Bin (International Journal of Technology, 2024)
In this paper, we provide a review of vehicle sensing and localization in autonomous driving. In autonomous driving, the significant and essential operation is accurate vehicular sensing. Vehicular sensing is the most demanding area of vehicular communications and has many envisioned applications in traffic safety and congestion avoidance. We begin by providing a brief overview of the Vehicular Ad Hoc Network (VANET) architecture, including its types. Additionally, we delve into in-vehicle sensors and their classification. The number of sensors in cars continues to grow, driven by their advantages in preventing injuries, enhancing driving performance, and supporting ubiquitous applications centered around vehicle sensing. We study and compare the current and existing techniques of localization (synchronous and asynchronous) and approaches for vehicle positioning, which is used for communication-based (e.g., GPS information) and reflection-based (e.g., RADAR Cameras). Also, we have also reviewed the vehicle-to-vehicle/infrastructure communications (V2X) with an emphasis on the 5G perspective.